Assessment of inflammatory suppression and fibroblast infiltration in tissue remodelling by supercritical CO2 acellular dermal matrix (scADM) utilizing Sprague Dawley models - Ngan Giang, Nguyen; Le, Linh Thi Thuy; Ngoc Chien, Pham; Trinh, Thuy-Tien Thi; Thi Nga, Pham; Zhang, Xin Rui; Jin, Yong Xun; Zhou, Shu Yi; Han, Jeonghun; Nam, Sun Young; Heo, Chan Yeong (Frontiers in Bioengineering and Biotechnology, 2024)
Human skin-derived ECM aids cell functions but can trigger immune reactions; therefore it is addressed through decellularization. Acellular dermal matrices (ADMs), known for their regenerative properties, are used in tissue and organ regeneration. ADMs now play a key role in plastic and reconstructive surgery, enhancing aesthetics and reducing capsular contracture risk. Innovative decellularization with supercritical carbon dioxide preserves ECM quality for clinica l use. The study investigated the cytotoxicity, biocompatibility, and anti-inflammatory properties of supercritical CO2 acellular dermal matrix (scADM) in vivo based on Sprague Dawley rat models. Initial experiments in vitro with fibroblast cells confirmed the non-toxic nature of scADM and demonstrated cell infiltration into scADMs after incubation. Subsequent tests in vitro revealed the ability of scADM to suppress inflammation induced by lipopolysaccharides (LPS) presenting by the reduction of pro-inflammatory cytokines TNF-α, IL-6, IL-1β, and MCP-1. In the in vivo model, histological assessment of implanted scADMs in 6 months revealed a decrease in inflammator y cells, confirmed further by the biomarkers of inflammation in immunofluorescence staining.Besides, an increase in fibroblast infiltration and collagen formation was observed in histologica l staining, which was supported by various biomarkers of fibroblasts. Moreover, the study demonstrated vascularization and macrophage polarization, depicting increased endothelial cell formation. Alteration of matrix metalloproteinases (MMPs) was analyzed by RT-PCR, indicating the reduction of MMP2, MMP3, and MMP9 levels over time. Simultaneously, an increase in collagen deposition of collagen I and collagen III was observed, verified in immunofluoresce nt staining, RT-PCR, and western blotting. Overall, the findings suggested that scADMs offer significant benefits in improving outcomes in implant-based procedures as well as soft tissue substitution.